Spatial Cognition VIII c - Stachniss, Cyrill; Schill, Kerstin; Uttal, David; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the proceedings of the 8th International Conference on Spatial Cognition, SC 2012, held in Kloster Seeon, Germany, in August/September 2012. The 31 papers presented in this volume were carefully reviewed and selected from 59 submissions. The conference deals with spatial cognition, biological inspired systems, spatial learning, communication, robotics, and perception.
Predicting What Lies Ahead in the Topology of Indoor Environments -- Object Categorization in Clutter Using Additive Features and Hashing of Part-Graph Descriptors -- Efficient Object Categorization with the Surface-Approximation Polynomials Descriptor -- Online Semantic Mapping of Urban Environments -- SURE: Surface Entropy for Distinctive 3D Features -- Dense Map Inference with User-Defined Priors: From Priorlets to Scan Eigenvariations -- Towards Geometric Mapping for Semi-autonomous Mobile Robots -- Tutorial on Quick and Easy Model Fitting Using the SLoM Framework -- Are Left-Right Hemisphere Errors in Point-to-Origin Tasks in VR Caused by Failure to Incorporate Heading Changes? -- The Effects of Visual Granularity on Indoor Spatial Learning Assisted by Mobile 3D Information Displays -- The Relationship between Coordination Skill and Mental Rotation Ability (Short Paper) -- Collaborating in Spatial Tasks: Partners Adapt the Perspective of Their Descriptions, Coordination Strategies, and Memory Representations -- Using Spatial Analogy to Facilitate Graph Learning -- Activity Effects on Path Integration Tasks for Children in Different Environments -- Influence of Rotational Axis and Gender-Stereotypical Nature of Rotation Stimuli on the Mental-Rotation Performance of Male and Female Fifth Graders (Short Paper) -- Towards a Revision of the Typology of Motion Verbs -- Assessing Similarities of Qualitative Spatio-temporal Relations -- The Mental Representation Derived from Spatial Descriptions is North-Up Oriented: The Role of Visuo-spatial Abilities -- Linguistic Principles for Spatial Relational Reasoning -- Extended Verbal Assistance Facilitates Knowledge Acquisition of Virtual Tactile Maps -- A Linguistic Ontology of Mode: The Use of Locations in Spatial Language -- Detecting Events in Video Data Using a Formal Ontology of Motion Verbs -- Relevance in Spatial Navigation and Communication -- Mental Travel Primes Place Orientation in Spatial Recall -- Linking Cognitive and Computational Saliences in Route Information -- Representing Space: Exploring the Relationship between Gesturing and Geoscience Understanding in Children -- Integration of Spatial Relations across Perceptual Experiences -- An iPad App for Recording Movement Paths and Associated Spatial Behaviors -- Detection of Object Onset and Offset in Naturalistic Scenes -- Wayfinding in Real Cities: Experiments at Street Corners -- Relocating Multiple Objects during Spatial Belief Revision.
Keywords: Computer science; Information storage and retrieval systems; Artificial intelligence; Computer simulation; Computer vision; Computer Science; Simulation and Modeling; Computer Imaging, Vision, Pattern Recognition and Graphics; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Information Systems Applications (incl. Internet).